EFEK FORTIFIKASI MINYAK IKAN TERHADAP KADAR OMEGA-3 DAN SIFAT SENSORI ROTI TAWAR SELAMA PENYIMPANAN [The Effect of Fish Oil Fortification on the Omega-3 Fatty Acids and Sensory Properties of White Bread during Storage] - Ribut Sugiharto; sri setyani; Nevy Rikafilanti (Jurnal Teknologi & Industri Hasil Pertanian, 2015)
White bread is one type of bread that contains low amount of sugar and generally consumed daily.  So far, white bread is used as a source of carbohydrates only, since other nutrients present in very small amounts.  One effort to improve the nutritional value of white bread is fortified with omega-3 fatty acids, derived from fish oil.  The purpose of this study was to determine the amount of fish oil added and storage time of white bread in order to produced white bread that contained high level of omega-3 fatty acid and good sensory properties.  This research was arranged within a Complete Randomized Block Design in factorial with three replications.  The first factor was the amount of fish oil added (0%, 1%, and 2%) and the second factor was the storage time (0, 1, 2, and 3 days).  The data were analyzed using Bartlett test for homogeneity and Tuckey test for additivity.  The data then were analyzed by using ANOVA to see the differences between treatments and analyzed  further using LSD at 5% level to determine the best treatment.  The results showed that the white bread obtained by adding 1% fish oil and 0 days storage time resulted as the best treatment with total omega-3 fatty acid 1.27%, aroma 4.43 (less fishy), taste 4.02 (less taste fish oil), texture 4.23 (soft), and the overall acceptance was 3.95 (like).Keywords:  fish oil, fortification, omega-3, white bread